Subacromial-First Approach to Minimize Infraspinatus Damage for Massive Rotator Cuff Tears Repair - Wittawat Boonyanuwat, M.D.; Chatchavan Charoenthamruksa, M.D.; Adisak Nartthanarung, M.D.; Pinkawas Kongmalai, M.D. (Arthroscopy Techniques)
We present a tendon-preserving approach for massive rotator cuff tears, focusing on the subacromial space rather than entering the glenohumeral joint. This technique aims to minimize iatrogenic injury to already compromised tendons, particularly the infraspinatus, while improving visualization and surgical efficiency. By accessing the subacromial space first, manipulation of retracted and weakened posterior cuff tissues is avoided, reducing the risk of further damage. The procedure is performed in the beach-chair position using 4 portals strategically placed for optimal visualization and precise anchor placement. After addressing the subscapularis tear, a double-row supraspinatus repair is completed without the need for intra-articular exploration. Preserving tendon integrity may enhance biomechanical stability and potentially decrease retear rates. Additionally, the retracted tendon edges often provide an indirect view of intra-articular structures, allowing for the management of biceps or labral lesions. Although selective intra-articular inspection may still be required in certain cases, this approach represents a paradigm shift in managing massive cuff tears. Future studies comparing outcomes, such as functional recovery and retear rates, with conventional intra-articular techniques are warranted to further validate this subacromial-first method.